1994
DOI: 10.2466/pms.1994.79.3.1131
|View full text |Cite
|
Sign up to set email alerts
|

Written Expression in Boys with Attention Deficit Disorder

Abstract: 32 boys, between the ages of 8 and 13 years, were identified on four teachers' and parents' rating scales (including the diagnostic criteria of the DSM-III for ADD) as showing attention deficits and hyperactivity (ADD + H; n = 10), attention deficits without hyperactivity (ADD-H; n = 11), or without ADD (attention deficits controls; n = 11). All subjects were administered Bender's Visual-motor Gestalt test and the Written Language Assessment. The ADD + H children produced significantly more errors on the Bende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 2 publications
4
33
1
1
Order By: Relevance
“…There has been an enormous increase in the number of studies evaluating the overlap of development syndromes or disorders in children and adults Results from different studies (Pitcher et al, 2003;Kaplan et al, 1997;Rasta and Eliot 1999) have shown an overlap of DCD with other neurodevelopment disorders and an overlap with other conditions have recently been published (Green and Baird 2005;Adib et al, 2005). Two studies from Kirby et al (2005); O'Hare and Khalid (2002), have both shown an association between motor difficulties and joint hypermobility syndrome while Green et al (2002) in their study highlighted the widespread prevalence of motor impairment in developmental disorders.…”
Section: Overlapping Of Dcd With Other Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an enormous increase in the number of studies evaluating the overlap of development syndromes or disorders in children and adults Results from different studies (Pitcher et al, 2003;Kaplan et al, 1997;Rasta and Eliot 1999) have shown an overlap of DCD with other neurodevelopment disorders and an overlap with other conditions have recently been published (Green and Baird 2005;Adib et al, 2005). Two studies from Kirby et al (2005); O'Hare and Khalid (2002), have both shown an association between motor difficulties and joint hypermobility syndrome while Green et al (2002) in their study highlighted the widespread prevalence of motor impairment in developmental disorders.…”
Section: Overlapping Of Dcd With Other Conditionsmentioning
confidence: 99%
“…High levels of overlap of DCD with other developmental disorders are shown from a number of researchers including: ADHD, Dyslexia and ASD (Pitcher et al, 2003;Rasta and Eliot, 1999;Kaplan et al, 1997); reading, attention and motor deficits (Kooistra et al, 2005); social and emotional and behaviour, anxiety, and depression (Sigurdsson et al, 2002); speech and language impairment (Hill, 1998); and social and communication impairment (Taylor et al, 2004).…”
Section: Overlapping Of Dcd With Other Conditionsmentioning
confidence: 99%
“…13 Evidence from a number of researchers [14][15][16] has shown overlap of DCD with other neurodevelopmental disorders. For example, in the Canadian population study, 17 23% of children showed signs of DCD, 8% met criteria for attention deficit hyperactivity disorder (ADHD), and 19% were categorized as dyslexic.…”
Section: Characteristics: Is This a Single Syndrome?mentioning
confidence: 99%
“…Additionally, the writing quality of students with ADHD symptoms was significantly poorer than controls, evidenced by greater numbers of repetitions in text, lower numbers of adjectives, and fewer subordinate clauses (Re, Pedron, & Cornoldi, 2007). Resta and Eliot (1994) examined the writing of 21 clinic-referred boys with ADHD. Compositions of the students identified as having ADHD scored significantly below controls in general writing ability, word complexity, and productivity.…”
mentioning
confidence: 99%